Concept mapping in computer-supported learning environments: a bibliometric analysis - Chang, Ching-Yi; Yang, Jie Chi (Interactive learning environments, 2023)
Concept mapping (CM) is widely used in educational settings as a teaching/learning or assessment tool. We conducted a bibliometric analysis and systematic review to provide an updated review on CM research in computer-supported learning environments. A total of 356 selected studies published from 1990 to 2020 were analyzed from the Web of Science database. The findings revealed an increasing and continuous focus on CM research. The leading journal for publishing CM research was Computers & Education, and the United States was the country with the most published studies. The most frequently used keywords were categorized into four clusters to represent the four main themes of CM research. Subsequent analysis showed that the most applied learning subject was environmental science or natural science; traditional computers/devices were the most used devices/hardware; higher education students were the most used samples; quantitative methods were the most used research methods; computers as mindtools were the most adopted learning strategy; and concept mapping assessment was the most used measurement tool in the CM research. These findings reveal the trends of CM research and provide future research directions and applications of practical education for researchers and educators.